Sistem Blockchain Berbasis Authentication dan Traceability Untuk Produk Batik dan Tenun Lokal Kreatif - Desi Ramayanti; Giri Purnama; Eriklex Donald; Eugene Feilian Putra Rangga; M. Julius Saputra; Prayoga Ade Pangestu (JSAI (Journal Scientific and Applied Informatics), 2025)
This research aimed to develop a blockchain-based system to ensure product authentication and traceability for creative textile products, with a case study on local Batik and Weaving SMEs in Bandung City. The main issue addressed was the widespread counterfeiting of products and the lack of transparency in the supply chain, which harmed both artisans and consumers. To address this, a system architecture was designed that utilized Hyperledger Fabric as the private blockchain platform, Node.js for the backend server, and IPFS for off-chain data storage. So far, the research has reached a technology readiness level (TRL) of 4, where the system prototype was validated in a laboratory environment. Key components such as the registration and verification module for SMEs by administrators, the product data input system, and the mechanism for generating a unique QR code for each product were successfully implemented. The system was developed to enhance consumer trust, protect product authenticity, and increase the market value of local creative textile products.